PENGARUH DEBT TO ASSET RATIO DAN TOTAL ASSET TURNOVER TERHADAP RETURN ON EQUITY - Wahyu Hari Prihantono; R. Nissa Purnamasari (The Asia Pacific Journal Of Management Studies, 2018)
This study aims to determine the effect of Total Assets Turn Over (TATO) Debt to Asset Ratio (Return) on Return on Equity in Food and Beverage Industry Sub Sector Companies Listed on the Indonesia Stock Exchange Period 2011-2016. The independent variables in this study are Debt to Asset Ratio (DAR) and Total Asset Turnover (TATO). The dependent variable is Return On Equity (ROE). The method used in this research is quantitative method. From the results of partial testing or t test shows that Debt to Asset Ratio has no significant effect on Return On Equity, while Total Asset Turnover has a significant negative effect on Return On Equity. Simultaneously or F Debt to Asset Ratio and Total Asset Turnover tests have a significant effect on Return On Equity.